Sleep knowledge, beliefs and practices in youth sports coaches and science support staff - Komarek, Z.; Holda, M.; Krzysztofik, S.; Spieszny, M.; Krzysztofik, M.; Filip-Stachnik, A. (Journal of Kinesiology and Exercise Sciences, 2022)
Background: The primary purpose of this study was to assess sleep hygiene knowledge among coaches and sports science support staff working with youth athletes, their sleep practices implemented with athletes, and their sleep education. Materials and methods: A sample of 139 Polish coaches and sports science support staff working with youth athletes volunteered to complete a survey focused on sleep monitoring, hygiene practices, and sleep education. The Sleep Beliefs Scale (SBS) was also included. Results: Overall sleep hygiene knowledge was inadequate for the whole sample (14.86 ± 2.70, score range 0 - 20; mean ± SD). However, the overall SBS score for science support staff was adequate (15.44 ± 2.71) and significantly higher than the inadequate score obtained by coaches (14.48 ± 2.65, p = 0.013). Less than half (48%) of coaches and science support staff promoted or administered sleep hygiene strategies, and only 17% monitored sleep of youth athletes. Most coaches and science support staff (only 35% of "Yes" responses) were not educated in sleep knowledge. However, there were significant differences between coaches and science support staff (28 % vs 46 %, respectively; p = 0.030) in their education in the field of sleep hygiene. Conclusions: Coaches working with youth athletes had inadequate overall sleep hygiene knowledge, while sports science support staff`s knowledge was adequate. Sleep hygiene strategies, sleep monitoring practices, and sleep education of coaches and science support staff seemed to be limited. We suggest that a broader approach to sleep education in youth sports staff might be necessary to improve sleep practices in youth athletes.